Adverse Drug Reactions Associated with Cancer Immunotherapy: Mechanisms, Clinical Spectrum, and Management Strategies - TM, Darshan; Ramaiah, Balakeshwa; Kumar, Delvin (Indian Journal of Pharmacy Practice, 2026)
Cancer immunotherapy has substantially reshaped contemporary oncology by improving survival outcomes across solid tumours and haematological malignancies. Immune Checkpoint Inhibitors (ICIs) and Chimeric Antigen Receptor T-cell (CAR-T) therapies enhance antitumor immune activity but are associated with a distinctive spectrum of immune-mediated adverse drug reactions, collectively termed immune-Related Adverse Events (irAEs). These toxicities may involve virtually any organ system and range from mild, self-limiting manifestations to severe, life-threatening complications requiring aggressive immunosuppression. This review provides a structured synthesis of the mechanisms, clinical manifestations, grading systems, and evidence-based management strategies for immunotherapy-associated adverse reactions, with particular emphasis on ICIs and CAR-T therapies. Updated international consensus recommendations are incorporated to support standardized clinical practice. Structured pharmacovigilance frameworks and multidisciplinary collaboration-including formal integration of clinical pharmacists-are emphasized as critical components to improve early detection, optimize toxicity management, and enhance patient safety outcomes.
Keywords: Cancer immunotherapy; CAR-T therapy; Immune checkpoint inhibitors; Immune-related adverse events; Pharmacovigilance